Solve for s.
-2(1 + 8s) = -3(2s + 4)
s =
Share
Lost your password? Please enter your email address. You will receive a link and will create a new password via email.
Please briefly explain why you feel this question should be reported.
Please briefly explain why you feel this answer should be reported.
Please briefly explain why you feel this user should be reported.
To solve the equation -2(1 + 8s) = -3(2s + 4), follow these steps:
1. Distribute the terms on both sides:
– Left side: -2 * 1 + (-2 * 8s) = -2 – 16s
– Right side: -3 * 2s + (-3 * 4) = -6s – 12
So the equation becomes:
-2 – 16s = -6s – 12
2. Next, get all the s terms on one side and the constant terms on the other side. Add 16s to both sides:
-2 = 10s – 12
3. Then, add 12 to both sides to isolate the s term:
-2 + 12 = 10s
10 = 10s
4. Now, divide both sides by 10 to solve for s:
s = 1
So, the solution is:
s = 1
Great job working through this! If you have more questions or need further assistance, feel free to ask!